Medieval Islamic Sectarianism. - Baker, Christine D.
1 online resource (116 pages)
Keywords: This book asks readers to re-examine their view of the Islamic world and the development of sectarianism in the Middle East by shining a light on the complexity and diversity of early Islamic society.